Ethical climate and the link between success and ethical behavior: An empirical investigation of a non-profit organization - Deshpande, Satish P. (Journal of business ethics, 1996)
This study examines the ethical climate and ethical practices of successful managers (n=206 managers) of a large non-profit organization. The influence of different dimensions of ethical climate on perceived ethical practices of successful managers were also investigated. Results show that a majority of the respondents perceive successful managers as ethical. Compared to previous research, managers in our sample were less optimistic about the relationship between success and ethical behavior. Those who believed that their organization had a “caring” climate perceived a strong positive link between success and ethical behavior. Those who believed that their organization had an “instrumental” climate perceived a strong negative link between success and ethical behavior.